Alternative off school Business Models that Enhance Multiple Intelligences in Kenyan Schools - David Maboko Nassiuma; Jonah N. Kindiki; Sammy K. Chumba (European Scientific Journal, ESJ, 2017)
Promotion of individual development and self-fulfillment amongst students in Kenya is among the national goals of education. To accomplish this goal it is imperative that, development of Multiple Intelligences in schools is put into perspective. To date, relatively little research has investigated the ways students Multiple Intelligences should be enhanced in Kenya. Consequently, this study was devised to examine alternative off school business management models that enhance Multiple Intelligences among secondary students in Kenya. The study was guided by the Multiple Intelligence Theory and Management Competency Framework. The study target population was 150 secondary schools in Elgeyo Marakwet. Data was collected using questionnaire, document analysis and interview. The data was analyzed qualitatively using thematic approach and quantitatively using percentages, means, standard deviation and simple linear regression. Data was presented in tables. The findings indicated that schools management was managing traditional models of enhancing multiple intelligences thus majority of the students’ abilities were not developed. Alternative off school business management models were found to be effective in enhancing multiple intelligences among students though majority of the schools had not adopted them. The study recommends that managing and facilitating entrepreneurship programmes should be promoted to enable students to show case abilities in different intelligences.